Effect of multi-cycle combustion on nox emission formation of hydrogen fuel in pulse detonation engine - Warimani, Mahammadsalman; Bellary, Sayed Ahmed Imran; Azami, Muhammad Hanafi; Khan, Sher Afghan; Muthuswamy, Sonachalam; Veerasigamani, Manieniyan (Semarak Ilmu Publishing, 2024)
Pulse Detonation Engines (PDE) have higher temperature combustion, which results in higher Nitrogen Oxides (NOx) emissions. The current study will investigate the formation of NOx using the computational fluid dynamics (CFD) method for multi-cycle combustion processes. The CFD model is created by varying the boundary conditions for hydrogen fuel. According to the CFD simulation, the maximum value of Nitrous oxide produced was 27000 ppm in the middle of the combustion tube during the first cycle, with a minimum range of 0-20 ppm produced at the start and end of both cycles. The computed results of a maximum rate of Nitrous Oxide of 100 microseconds are consistent with previous literature. In the PDE analytical analysis, hydrogen fuel had the highest Emission Index of Nitrous Oxide (EINOx) of 58.64 g/kg of fuel, and methane fuel had the lowest EINOx of 10.06 g/kg. In CFD analysis at 10 microseconds, RAM-jets produced around 100 g/kg of fuel, while PDE produced 50 g/kg of fuel in EINOx.